Introduction to NJWLS 2023-1 - Buch, Anders (Nordic Journal of Working Life Studies, 2023)
I am delighted to present the first issue of the 13th volume of Nordic Journal of Working Life Studies. In this issue, you will find four research articles from Finland, Sweden, Denmark, and Iceland.